The music business and recording industry: delivering music in the 21st century - Hull, Geoffrey P. (Routledge, 2011)
A brief but comprehensive examination of how records are made, marketed, and sold. This new edition takes into account the massive changes in the recording industry occurring today due to the revolution of music on the web.